Acoustic radiation force impulse imaging of the testes: A preliminary experience - D'Anastasi, M.; Schneevoigt, B.S.; Trottmann, M.; Crispin, A.; Stief, C.; Reiser, M.F.; Clevert, D.A. (Clinical hemorheology and microcirculation, 2011)
Purpose: Acoustic radiation force impulse imaging (ARFI) is a newly developed technique for the sonographic quantification of tissue elasticity. It has been used in the assessment of various abdominal organs. The testes are extraabdominal organs with limited overlying tissue, making them ideally suited to ARFI assessment. To our knowledge no published data exist on ARFI elastography of the testes. Method: 23 male volunteers (mean age 45.13 ± 17.3, range 23–75) with no known testicular pathology underwent normal B-mode sonography with ARFI elastometry of both testes using a Siemens Acuson S2000™ (Siemens Healthcare, Germany) system. 15 measurements were performed on each testis; 5 each in the upper pole, middle portion and lower pole. Results were statistically evaluated. Results: 95% of the SWV values were found to lie within the reference interval ranging from 0.62 to 1.01 m/s. There was a significant association between measured SWV and age (P = 0.0056) and testicular volume (P = 0.0003). Conclusion: ARFI elastometry proved to be feasible in the assessment of testicular stiffness. Older age and lower testicular volumes were associated with increased parenchymal stiffness. Further studies with more subjects may be required to define the normal range of values for each age group.